Fragmentation mechanisms for Methane induced by 55 eV, 75 eV and 100 eV electron impact. (August 2015) - Wei, B; Wang, X; Zhang, Y; Hutton, R; Zou, Y
Synopsis: CH4 2+ break up into three or more fragments in one or two-step processes were studied, our result shows that there are three reaction channels to form CH2 +, H +, and H, one synchronous concerted reaction channel and two two-step reaction channels. For even more complicated fragmentation processes of CH4 2+ dications, the fragmentation mechanism can still be identified in the present measurements.